Neurodevelopmental outcomes of a randomised trial of intact cord resuscitation. (25th June 2020) - Isacson, Manuela; Gurung, Rejina; Basnet, Omkar; Andersson, Ola; KC, Ashish
Abstract: Aim: It has been suggested that intact cord resuscitation can reduce the risk of brain damage. We investigated the effects on neurodevelopment at two years of age. Methods: This study was performed in Kathmandu, Nepal. In 2016, 231 late preterm and term infants born vaginally and not breathing were randomised to resuscitation with an intact cord or the standard practice of early cord clamping (CC). At two years of age, the World Health Organization's Infant and Young Child Development tool was used to assess the child's neurodevelopment, during telephone interviews with caregivers. Results: We followed up 138 infants (59.7%) at a mean age of 24.8 ± 0.8 months. A significant difference was seen in the development for age Z ‐score, between the group resuscitated with an intact umbilical cord and the group resuscitated with early CC. The median (range) scores were 1.0 (0.1‐2.1) vs 0.9 (−2.0 to 1.8), respectively ( P = .04). There was no difference in the motor, language‐cognitive and socio‐emotional domains. Conclusion: Neurodevelopment improvements were observed at two years of age in infants resuscitated with an intact rather than early clamped umbilical cord. No definitive conclusions could be drawn due to protocol violations and a low follow‐up rate. More research is needed.